Sectoral Herding Contagion Between Oil Rich Countries - Syed Faisal Hassan Bukhari; Saif ullah Khurram; Saparova Botagoz; Ghulam Abbas, (Dialogue Social Science Review (DSSR), 2025)
This paper examines the spread of herd behaviour in the oil-rich stock markets of Saudi Arabia (KSA) and Iraq, particularly amidst the heightened uncertainty of the COVID-19 pandemic, considering the degree of market integration. A modified Cross-Sectional Absolute Deviation (CSAD) measure, recognized as an indicator of herding, is employed to explore the presence of herding contagion before and after the COVID-19 crisis. The findings reveal that herding behavior from dominant markets influences other integrated markets, both before and after the pandemic. Specifically, herding in the Iraqi stock market is significantly impacted by activity in the integrated Saudi Arabian market. However, the energy and healthcare sectors did not exhibit herding contagion. This highlights the importance of market participants exercising caution in predicting this phenomenon in integrated markets under various conditions. The findings hold substantial implications for governments, investors, and policymakers, enhancing their understanding of market dynamics and aiding in portfolio diversification strategies.